2018
DOI: 10.1111/anae.14321
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a novel cricothyroidotomy introducer in a simulated obese porcine model: a randomised crossover comparison with scalpel cricothyroidotomy

Abstract: The Difficult Airway Society 2015 guidelines for management of unanticipated difficulties in tracheal intubation in adults have generated much discussion regarding Plan D: emergency front-of-neck access with a scalpel-bougie cricothyroidotomy technique. There is concern that this technique may not provide an adequate pathway for the bougie and subsequently the tracheal tube, especially in obese patients with deeper airway structures. This could lead to the formation of a false passage, trauma and failure. A no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
2
4
1
Order By: Relevance
“…Consistent with the findings in the´wet´sheep model of morbidly obese neck, we have not observed any differences in insertion times between the cannula and scalpel-bougie technique [25]. However, when compared to the non-obese or slim-neck animal models, longer insertion times were reported especially for cannula technique [2,13,16,[25][26][27]. In our study, the cannula technique was successfully accomplished in less than 60 seconds in only three animals (27%)…”
Section: Plos Onesupporting
confidence: 89%
See 2 more Smart Citations
“…Consistent with the findings in the´wet´sheep model of morbidly obese neck, we have not observed any differences in insertion times between the cannula and scalpel-bougie technique [25]. However, when compared to the non-obese or slim-neck animal models, longer insertion times were reported especially for cannula technique [2,13,16,[25][26][27]. In our study, the cannula technique was successfully accomplished in less than 60 seconds in only three animals (27%)…”
Section: Plos Onesupporting
confidence: 89%
“…The increased pretracheal soft tissue depth represents an additional challenge in manually palpating the cricothyroid membrane. As a result, a cricothyroid membrane was punctured in 74% of our animals, which replicated the previous data in pig's larynx simulating the obese neck [26]. The cricothyroid membrane identification can be improved by the use of ultrasonography.…”
Section: Plos Onesupporting
confidence: 87%
See 1 more Smart Citation
“…These 11 failures using the scalpel‐bougie technique contrast with the cannula technique where simple manoeuvres or a second attempt often resulted in success after an initial failure. A high rate of false passage of bougie and tracheal tube (65%) has been shown in an obese porcine benchtop model using a scalpel‐bougie technique . The chance of false passage increases when the trachea is found deep within tissues (as occurs in obesity) which is relevant to the difficult airway .…”
Section: Discussionmentioning
confidence: 99%
“…Yeow et al. found a median one‐second difference in time to insertion of a tracheal tube with successful ventilation using a novel cricothroidotomy introducer compared with scalpel cricothroidotomy (85 s vs. 84 s, respectively) . However, despite the novel introducer having the greater median, the authors concluded its insertion was faster, with a p value (Wilcoxon's Signed Ranks (WSR) test) of 0.030.…”
mentioning
confidence: 99%